PESONA PEMIKIRAN POLITIK MUHAMMAD ABDUH - Ridwan Ridwan (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
This writing is aimed at discussing the thought of Muhammad Abduh and addressing his social condition and influence in Islamic modern politics. Abduh was Islamic modern scholar that campaigned for the change based on rationale not religious dogmatism. His campaign can be seen from his effort to accommodate syari’ah basic principles with contemporary standards. Abduh’s movement has colored Egyptian politics. Abduh’s reform was started from changing education system critically according to modern method. He campaigned for Pan-Islamism and Islamic reform. He separated between essential and non-essential elements. He also perpetuated fundamental aspects and abandoned accidental historical aspects. Thus, he proposed several elements: returning to original source, Al-Qur’an and Hadits; using rationale proportionally in order to suit contemporary interpretation and standards. Then, according to Abduh, political organization cannot be ruled by Islamic teaching but the chorus. Therefore, Abduh’s reform emphasized more in freedom to determine the form of state: Khalifah or western democracy